KDM2A/B lysine demethylases and their alternative isoforms in development and disease - Vacík, Tomáš (Nucleus, 2018)
Aberrant levels of histone modifications lead to chromatin malfunctioning and consequently to various developmental defects and human diseases. Therefore, the proteins bearing the ability to modify histones have been extensively studied and the molecular mechanisms of their action are now fairly well understood. However, little attention has been paid to naturally occurring alternative isoforms of chromatin modifying proteins and to their biological roles. In this review, we focus on mammalian KDM2A and KDM2B, the only two lysine demethylases whose genes have been described to produce also an alternative isoform lacking the N-terminal demethylase domain. These short KDM2A/B-SF isoforms arise through alternative promoter usage and seem to play important roles in development and disease. We hypothesise about the biological significance of these alternative isoforms, which might represent a more common evolutionarily conserved regulatory mechanism.